Autologous repair of an internal carotid artery aneurysm by resection, caliber reduction, and external mesh tube reinforcement in a 9-year-old boy - AK, KORAY (MOSBY-ELSEVIER, 2007)
Extracranial internal carotid artery aneurysms in children are rare, with a reported incidence of 0.5% to 1.9% in internal carotid artery aneurysm operations compared with all carotid operations in adult patients. We report a case of surgical reconstruction of an extracranial internal carotid artery aneurysm in a 9-year-old boy. Our patient complained of episodic neck pain on the left site under the mastoid process for the last year. The child was otherwise healthy. Autologous reconstruction without graft interposition was planned. Surgical repair was performed by resection of the main body of the aneurysm and restoration of the arterial continuity with end-to-end anastomosis. Because nondilated proximal and distal vessels could not be approximated, the most distal end of the aneurysm was tapered over a mandril. To prevent redilation, a tubular polyester external stent was fitted around the diseased segment.
Keywords: FIBROMUSCULAR DYSPLASIA; CHILD; MANAGEMENT; GRAFTS